Občutljivost za antibiotike pri povzročiteljih nezapletenega cistitisa v Sloveniji - Ribič, Helena (Zdravniški vestnik, 2024)
Background: Acute uncomplicated cystitis in women is a common reason for antibiotic treatment in the outpatient clinic of family doctors. Microbiological diagnostics is not indicated; treatment is generally empirical and based on guidelines and recommendations. Therefore, we do not have representative data on the incidence and sensitivity of pathogens from regular laboratory work. Special targeted research is needed. Methods: We present the results of the prospective research conducted in four regional laboratories of the Centre for Medical Microbiology NLZOH between 15 September 2017 and 31 December 2019. We included 110 female patients with suspected acute uncomplicated cystitis who completed a questionnaire and submitted urine samples for microbiological examination. Results: The result of urine examination was positive in 79 patients (71.8%). Among all isolates, the most common bacterium was Escherichia coli (74%), followed by Staphylococcus saprophyticus (10%), and others. The susceptibility of E. coli to trimethoprim with sulfamethoxazole was 85.5%, to nitrofurantoin 98.4%, and to fosfomycin 100%. S. saprophyticus isolates were susceptible to the tested antibiotics except for fosfomycin, against which the bacterium is intrinsically resistant. The total susceptibility of all isolates was 85.8% - 88.2% for trimethoprim with sulfamethoxazole, 88.1% - 95.2% for nitrofurantoin, 73.8% - 80.8% for fosfomycin, 72.6% for ampicillin and amoxicillin, 97.7% for cefadroxil, and 98.9% for amoxicillin with clavulanate acid. A comparison with the results of monitoring bacterial resistance as part of the regular work of microbiological laboratories shows significant differences for most of the tested antibiotics. Conclusion: The research results show a relatively good susceptibility of the causative agents of acute uncomplicated cystitis to oral antibiotics, the only exception being amoxicillin.
Keywords: Escherichia coli; fosfomicin; nitrofurantoin; Staphylococcus saprophyticus; trimetoprim sulfametoksazol